Polumarkov’ models for an optimum management of informative interaction of computer systems - Гузій, М. М. (Problems of Informatization and Control, 2009)
Polumarkov’ models for an optimum management of informative conflicts in computer networks are developed. The typical problem statement of optimum dynamics of informative conflicts management is  grounded,  the  tasks  of  hierarchical  informative  interface  management  in  the  computer  systems features are considered